Entorno social cultural y su incidencia en el desarrollo cognitivo de los niños de 4 años - Poma Ortega, Gabriela Elizabeth (2015)
This research work concerns the impact of cultural and social environment in the cognitive development of children from 4 years of the Education Unit PRAGA. The theories of cognitive development according to Piaget and Vygotsky reveal that the influence of environment helps in acquiring intellectual skills to construct their own knowledge. If this Social environment - Cultural is not given in the first years of life experiences and appropriate meaningful learning, impair the ability of basic mechanisms of attention, abstraction of the first concepts and the ability to solve simple problems, this research applies the inductive method refers to the meeting of all components of induction, ie prior knowledge to achieve overall results, and the deductive method because it is part of a previously established general problem, which is the social and cultural environment, which It will lead to specific results obtained from the application of surveys to twelve teachers and twenty eight legal representatives reflecting how it affects the social environment - culture in cognitive development…….